Contributions of Basic Cognitive Processing to Chinese Reading: The Mediation Effect of Basic Language Processing - Yang, Xiujie; Peng, Peng; Meng, Xiangzhi (Frontiers in Psychology, 2019)
Prior research has mostly focused on either domain-specific precursors or domain-general precursors of reading development, but relatively little is known about their concurrent effects on reading, especially for Chinese beginning readers. The present study examined the domain-general processing (executive function, attention, and visual-spatial perception) and domain-specific processing (phonological awareness, morphological awareness, orthographic awareness, and rapid naming) of Chinese senior kindergarten children and followed up on their word reading and reading comprehension after 14 months when they got into first grade. Results revealed that both domain-general and domain-specific processing contributed to Chinese word reading and reading comprehension. Specifically, domain-specific abilities, including morphological awareness, orthographical awareness, and rapid naming measured in kindergarten, predicted later Chinese word reading. One of the domain-general factors, sustained attention in kindergarten, predicted later reading comprehension. Results further indicated that the effect of domain-general processing on later reading performance (word reading and reading comprehension) was mediated by domain-specific processing.